Critiques et enjeux du Dark tourism à travers la focale sud-africaine - Fabrice Folio (EchoGéo)
Research into visits associated with dramatic episodes, suffering and death is relatively recent among francophone scholars. But this theme has attracted more attention among English speakers where the term ‘dark tourism’ is used. Such attractions are easily open to criticism. Controversy usually crystallizes around whether a marriage between pain and suffering, and the tourism and recreation industry is really feasible. We maintain that the plurality of underlying challenges should prevent any simplistic debate; there are many issues involved in the recognition of ‘dark tourism’. We advance some thoughts in this research domain, drawing on experiences in South Africa.